Fractional dynamics of a system with particles subjected to impacts - Machado, J. A. Tenreiro (2011)
This paper studies the dynamics of a system composed of a collection of particles that exhibit collisions between them. Several entropy measures and different impact conditions of the particles are tested. The results reveal a Power Law evolution both of the system energy and the entropy measures, typical in systems having fractional dynamics.